Analysis of Marketing Strategies for Women-Only Fitness Centers in Madiun City within Global Industry Trends - Dinesh Basti Farani; Dinta Sugiarto; Ira Hasti Priyadi; Agustinus Doedyk Setiyawan (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study analyzes the marketing strategies of women-only fitness centers, exemplified by Fitday Studio Madiun, within the broader context of global industry trends and local socio-economic dynamics. Driven by a growing awareness of preventive health and women's specific needs for privacy and comfort in exercise environments, the women-only fitness segment is experiencing rapid growth. This research employs the 7Ps marketing mix and SERVQUAL model to evaluate Fitday Studio's approach, identify key motivations and barriers to female participation, and assess its market positioning. Findings indicate that Fitday Studio effectively leverages its all-female staff (